Effectiveness, complications and reproductive outcome of selective chemoembolization with methotrexate followed by suction curettage for caesarean scar pregnancy - A prospective observational study. (October 2019) - Stępniak, Anna; Paszkowski, Tomasz; Jargiełło, Tomasz; Czuczwar, Piotr
Abstract: Objective: Caesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy implanted in a previous caesarean scar. Selective chemoembolization with methotrexate (SCEM) followed by suction curettage (SC) is one of the treatment options for CSP. The aim of the study was to assess the effectiveness, complications and reproductive outcome of SCEM followed by SC in the treatment of CSP. Study design: All cases of CSP treated with SCEM followed by SC between 2015 and 2018 were prospectively followed-up to assess short and long-term outcome. All patients hospitalized with the suspicion of CSP during the study period were included in the study. Gelatine sponge was used as embolic material to avoid permanent damage of the uterus and minimise the possible impact on fertility. Haemoglobin (Hb) and beta human chorionic gonadotropin (β-hCG) levels, normalization of menstrual cycle, complications after the procedure and subsequent fertility were assessed. Results: Twenty-two patients diagnosed with CSP underwent SCEM followed by SC. The procedure was effective in 20 cases (91%). In two cases additional SCEM was required before attempting SC due to persistent vascularity on ultrasound in one case and abnormal uterine bleeding in the second one. No complications were observed during the procedures, none of the patients required a hysterectomy. Follow-up ranged from 9 to 36 months. In short-term follow-up no significant complications occurred, only minor ailments such as uterine cramping and nausea were reported by 8 patients. In long-term follow-up 8 patients reported at least one complication, such as hypomenorrhea, amenorrhoea or were diagnosed with Asherman syndrome. Ten patients tried to conceive and 4 out of them achieved a pregnancy (all in less than 12 months) and delivered by caesarean sections between 35 and 39 weeks. One patient reported recurrent miscarriage. Conclusion: SCEM followed by SC appears to be an effective treatment option for CSP. The method seems to be safe in short-term follow-up. However, complications were observed in long-term follow-up. Therefore, patients should be informed about the risk of complications interfering with future fertility, such as intrauterine adhesions and/or amenorrhea.